2019
DOI: 10.1097/sap.0000000000001848
|View full text |Cite
|
Sign up to set email alerts
|

Role of Postoperative Anticoagulation in Predicting Digit Replantation and Revascularization Failure

Abstract: Purpose The use of intravenous heparin after digit replantation or revascularization (DRR) varies greatly. The insufficient evidence presents a lack of clinical equipoise needed for a randomized trial; as such, a matched propensity score analysis was performed to evaluate the role of postoperative anticoagulation after DRR. The purpose of this study was to determine if the use of postoperative therapeutic anticoagulation reduced the risk of digit failure. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 34 publications
0
25
1
Order By: Relevance
“…Therapeutic intravenous anticoagulation administered postoperatively was not shown to be predictive of failure in our cohort in a previously published study (Retrouvey et al, 2019). In the current study, leeching was an important predictor of both early and late failure, implicating venous congestion as a common cause of failure.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Therapeutic intravenous anticoagulation administered postoperatively was not shown to be predictive of failure in our cohort in a previously published study (Retrouvey et al, 2019). In the current study, leeching was an important predictor of both early and late failure, implicating venous congestion as a common cause of failure.…”
Section: Discussioncontrasting
confidence: 64%
“…The use of prophylactic and therapeutic anticoagulation was applied on a case-by-case basis when one or more of these parameters was abnormal rather than applying a standard institutional protocol. This is because the benefits of its routine use have not been shown to outweigh the risks (Retrouvey et al., 2019). Leeching or therapeutic anticoagulation in the form of heparin, dextran or heparin with dextran were applied selectively in patients showing evidence of vascular insufficiency.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we used this collection of predictors to generate a propensity score for each patient. As another example, Retrouvey et al, in their retrospective study on postoperative anticoagulation in digit replantation and revascularization outcomes, 14 recognized that certain variables may have influenced both the use of anticoagulation and the success of replantation and revascularization. Thus, they generated propensity scores that reflected patients’ probability of having received anticoagulation; predictors used to generate the scores included age, smoking status, digit injury mechanism, number of injured digits, procedure type, and use of a vein graft.…”
Section: Discussionmentioning
confidence: 99%
“…A 2019 randomized and single-blinded study found no significant difference between the three groups: (1) no heparin; (2) low dose heparin (10,000 IU/day); and (3) high dose heparin (starting at 15,000 IU/day and adjusted to achieve activated partial thromboplastin time of 1.5-2.5 times the patient's baseline) [37] . Studies with various therapeutic evidence levels have supported these conclusions [38,39] . In addition to dose, one study found increased survival with progressive weaning of heparin rather than abruptly discontinuing it [40] .…”
Section: In the Literature: Uncertainty And Disagreementmentioning
confidence: 94%